Strategi Kebijakan Ekonomi Sirkular Melalui Inovasi Desain Kemasan Ramah Lingkungan untuk Gula Merah Pulau Sebesi - Dwi Ayu Setiowati; M. Reza Andrea Putra; Risma Pitriani Nuryana (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2026)
This community service was carried out at the Sebesi Island Coconut Brown Sugar Artisans Group, South Lampung Regency, which faced the problem of low product competitiveness due to the use of conventional plastic packaging that was simple, unattractive, and environmentally unfriendly. This topic was chosen because it is relevant to the issue of the plastic waste crisis and the urgency of implementing a circular economy in island regions that are vulnerable to environmental pollution. The objective of this activity was to improve the hard and soft skills of partners through the innovation of environmentally friendly packaging designs based on local materials, while also increasing the economic value of coconut brown sugar products. The community service was carried out using a participatory approach through socialization, training, co-design of packaging, and assistance with production and marketing for 40 partners consisting of brown sugar craftsmen, BUMDes administrators, and local natural material weavers. The results of the activity showed an increase in the partners' skills in product design and packaging, strengthening of soft skills in the form of confidence and marketing readiness, as well as an increase in the selling value and image of the product in the local market. This activity confirms that environmentally friendly packaging innovation based on local resources is an effective strategy in empowering MSMEs as well as implementing a circular economy at the village level.